PAX9 mutation of non-syndromic hypodontia in a Malaysian family - Mohamed Idrus, Nur Farahiyah; Rosley, Nur Syahira; Irfanita, Nining; Ardini, Yunita Dewi; Arief Ichwan, Solachuddin Jauhari; Lestari, Widya (University of Indonesia, 2016)
Objective: Hypodontia is portrayed by the missing of one to six numbers of teeth. PAX9 is one of the genes that caused non-syndromic hypodontia. We aimed to investigate the PAX9 mutation of non-syndromic hypodontia with clinical variability in a Malaysian hypodontia family. Methods: Clinical examinations for all participants whilst orthophantomogram (OPG) was taken for hypodontia patient only. Saliva was collected for genetic analysis. Direct sequencing was performed by using exon 2and 3 of PAX9 gene. Results: 3 out of 5 family members are affected with hypodontia. The mother has missing posterior tooth and her daughters have missing anterior teeth. The point mutation was identified on exon 2 on patient 1C; c.620G>T and on exon 3 on patients 1B; c.465delG, 1C; c.273T>G, 1D; c.462delT. Conclusions: Our findings suggested those identified points mutations of PAX9 either on exon 2 or exon 3 is responsible for the hypodontia phenotype in this family.